Performance Medicine: a novel and needed paradigm for proactive health care - Joseph, Richard J.; Pojednic, Rachele M. (Frontiers in Sports and Active Living, 2023)
Performance Medicine is an emerging clinical practice that holds immense promise for advancing preventive health. To date, however, the concept remains imprecise, disorganized, and commercialized. The purpose of this perspective article is to define characteristics, core tenets, and practice standards to help build a common framework. We define performance broadly as “one’s capacity to bring energy and attention to what matters most in a given moment”. Performance Medicine, therefore, is predicated on the thesis that the critical practices that enhance one’s daily wellbeing simultaneously increase both lifespan and healthspan. As a clinical practice, Performance Medicine is proactive and preventive. It focuses on the immediate and actionable strategies to address one’s physical, mental, and emotional capabilities every day. The practice employs a values-centered approach that begins with a discovery process to elucidate the client’s deeply held beliefs about their health status, life mission and goals, vision for optimal wellbeing, and motivations for change. Subsequent diagnostics and therapies combine evidence-based practices from multiple medical specialties including internal medicine, sports medicine, obesity medicine, integrative medicine, and others. This is complemented by the most recent scientific advancements in nutrition, exercise physiology, sleep, and recovery. The Performance Medicine prescription incorporates a personalized combination of lifestyle-based behavior change practices, evidence-based diagnostics and risk reduction therapies, ongoing monitoring, and community support. Finally, the iterative and incremental process towards enhanced and sustained health is guided and supported by a trusted partnership between the client and a team of expert practitioners and coaches.